Beyond the color: A structural insight to eosin-based lakes. (May 2017) - Anselmi, Chiara; Capitani, Donatella; Tintaru, Aura; Doherty, Brenda; Sgamellotti, Antonio; Miliani, Costanza
Abstract: Motivated by the fugitive and undisclosed nature of eosin-derived pigments as used by Vincent van Gogh, this paper presents the syntheses of monometallic and historical bimetallic eosin-based lakes and structural elucidation by MS, ATR-FTIR and NMR. Specifically two monometallic (Al, Pb) and several bimetallic lakes (on varying Al and Pb constituents) have been synthesized and examined alongside two reference compounds: eosin disodium salt and eosin Y. Resulting monometallic lake complexes are 2:1 adducts (dye:metal) with the carboxylic group coordinating the metal. In historical lake preparations, no correlation between the coordinating metals and the resulting lake color can be made. On production and investigations of different eosin lake substrates, two main anchored species have been distinguished: H-bonded for eosin onto Pb-substrates and a further bridged bidentate for eosin onto alumina. A prominent tendency to form 2:1 eosin:Pb adducts emerged in each Pb-containing recipe. Evidence concerning historical lakes suggests that eosin can diversely coordinate to metals thus producing a variety of nuances in according to experimental pH and reaction conditions. This behavior may well explain observed discrepancies between historical recipes and experimental findings regarding the coordination of eosin to one or more metals. Highlights: Mono- and bimetallic eosin lakes were synthesized and structurally elucidated. Historical bimetallic lakes are either anchored onto substrate or simply mixed within. Within anchored lakes two kinds emerged: H-mediated bonded and bridged bidentate. Monometallic model Pb-lake, resulted ubiquitous within the historical lakes. The pH of reaction demonstrated to determine the final lake color.